Body size, body composition and glucose tolerance with special reference to adult height, body surface area, fat and lean body mass - Rehunen, Simo (fi=Turun yliopisto|en=University of Turku|, 2021)
Body size and body composition have long interested mankind and their assessments are considered key factors for the evaluation of overall health status. Although the role of obesity – mostly applying body mass index (BMI) as a marker of obesity – in insulin resistance and type 2 diabetes (T2D) is well established, it is not fully understood how body size and body composition, i.e lean and fat mass, are associated with glucose tolerance/metabolism and development of T2D. This study aimed to investigate the association of the combined effect of adult height and BMI, and body surface area (BSA) on glucose tolerance among middle-aged individuals at increased cardiovascular risk (n = 2659) from the Harjavalta Risk Monitoring for Cardiovascular Disease Project, and the association of the combined effect of lean and fat mass on glucose regulation and subsequent development of T2D among persons without diabetes at baseline (n = 1617 and n = 704, respectively) from the Helsinki Birth Cohort Study (HBCS). Anthropometric measures and oral glucose tolerance test (OGTT) were performed in all individuals, and body composition was assessed in HBCS. Taller people had lower 2-hour plasma glucose (2hPG) than shorter people, up to a BMI of 35 kg/m2. The smaller the adjusted BSA of the person, the higher the proportion of newly diagnosed T2D based on 2hPG. High lean mass index (lean mass/height2) accompanied with high fat mass index (fat mass/height2) was associated with insulin resistance in men, whereas in women lean mass had little influence on glucose tolerance. Higher adiposity increased 2hPG values. The combination of high fat mass index and high lean mass index was associated with an elevated risk of developing T2D during a 15-year follow-up. There is a possibility that the diagnosis of T2D made by an OGTT is a false positive result in a relatively smaller person, and a false negative result in a relatively larger person. Hence, it is questionable whether OGTT has a major clinical importance. Contrary to a general belief muscle mass – the predominant part of lean mass – is not protective against T2D. High muscle mass accompanied with fatness seems to be detrimental for glucose homeostasis and predict development of T2D. Fatness is the major determinant of glucose intolerance.

Kehon koon ja koostumuksen vaikutus glukoosinsietoon – mielenkiinnon kohteina aikuispituus, kehon pinta-ala sekä kehon rasvaton ja rasvamassa Kehon koko ja koostumus ovat kiehtoneet ihmisiä kautta aikojen, ja niillä on keskeinen asema terveyttä tutkittaessa. Vaikka lihavuuden merkitys insuliini-resistenssiin ja tyypin 2 diabetekseen on hyvin tunnettu, ei tiedetä täysin, miten kehon koko ja koostumus eli rasvamassa ja rasvaton massa vaikuttavat glukoosinsietoon ja diabeteksen kehittymiseen. Tämän tutkimuksen tavoitteena oli selvittää aikuispituuden ja lihavuuden yhteisvaikutus sekä kehon pinta-alan yhteys glukoosinsietoon keski-ikäisillä sydän- ja verisuonitautiriskihenkilöillä (n = 2659) Harjavallan valtimotautien ehkäisy- projektista. Lisäksi selvitettiin rasvattoman ja rasvamassan yhteisvaikutus glukoo-sinsäätelyyn ja diabeteksen kehittymiseen ei-diabeetikoilla (n = 1617 and n = 704, vastaavasti) Helsingin syntymäkohorttitutkimuksesta (HBCS). Antropometriset mittaukset ja glukoosirasituskoe tehtiin kaikille tutkituille ja kehon koostumuksen mittaus HBCS:n osallistujille. Kahden tunnin glukoosiarvo oli matalampi pitkillä kuin lyhyillä henkilöillä aina painoindeksiin 35 kg/m2 asti. Mitä pienempi kehon pinta-ala, sitä suurempi todennäköisyys on saada diabetesdiagnoosi kahden tunnin glukoosiarvon perusteella. Suuri rasvaton massa -indeksi (rasvaton massa/pituus2) yhdistyneenä suureen rasvamassaindeksiin (rasvamassa/pituus2) oli yhteydessä insuliini-resistenssiin miehillä, kun taas naisilla rasvaton massa -indeksi ei vaikuttanut glukoosinsietoon. Kahden tunnin glukoosiarvot nousivat rasvakudoksen lisään-tyessä. Suuri rasvaton massa -indeksi suuren rasvamassaindeksin kanssa oli yhteydessä diabeteksen kehittymiseen 15 vuoden seurannan aikana. On mahdollista, että pienikokoisilla henkilöillä glukoosirasituskokeen perusteella tehty diabetesdiagnoosi on väärä positiivinen, kun taas kookkailla väärä negatiivinen. On siis kyseenalaista, onko glukoosirasituskokeella enää kliinistä merkitystä. Vastoin yleistä uskomusta lihasmassa, joka muodostaa suurimman osan rasvattomasta massasta, ei suojaa diabetekselta. Sen sijaan lihavilla suuri lihas-massa vaikuttaa olevan haitallista glukoosiaineenvaihdunnalle ja altistaa diabeteksen kehittymiselle. Rasva on glukoosi-intoleranssin tärkein tekijä.